Four new species of the genus Coelotes (Araneae: Amaurobiidae) from China - Xu, Xiang; Li, Shuqiang (Zootaxa, 2006)
Four new Coelotinae species are reported: Coelotes capacilimbus spec. nov., C. conversus spec. nov., C. indistinctus spec. nov. and C. introhamatus spec. nov. A detailed description and illustrations of each new species are presented and differences with related species are discussed. A distribution map of all four new species is provided.